Women involvement in large-scale agricultural production and information utilization (2005)
The aim of this study is to identify the place of women in the use of information in large scale agricultural development process in Ijaye community of Akinvele Local Government Aiea of Oy o State. This is with a view to providing valuable data for government. NGOs and other Policy making bodies, to guide in developing the agricultural development programmes. Two hundred and forty copies of a questionnaire were administered Ip respondents, which include women farmers and extension workers. Also, data wet e collected through the focus group discussion oral interview and existing comparative literature. It was revealed that only a very small percentage of women farmer were involved in fairly large-scale agriculture.' Factors responsible for this include non-allocation of land to women, lack of relevant information on agriculture and lack of funds. Nevertheless, the very few that were engaged in fanning utilize the information at their disposal maximally.